Contemporary developments in Green (environmental) HRM scholarship. Issue 2 (19th January 2016) - Renwick, Douglas W.S.; Jabbour, Charbel J.C.; Muller-Camen, Michael; Redman, Tom; Wilkinson, Adrian
Abstract : This article reviews the contemporary literature on Green Human Resource Management (GHRM) to contextually frame the seven articles appearing in this Special Issue. Review findings reveal the embedded nature of GHRM workplace-level practices and additional research needing to focus on HR systems, individual behaviors and emerging theoretical lenses. As a set, the articles herein span green recruitment, competencies, employee participation, financial/environmental performance links, and contextual issues utilizing national culture, paradox, and stakeholder theories. By recognizing such multi-level dynamics, HRM scholars and practitioners can enhance GHRM initiatives that stimulate progress toward workplace environmental sustainability.